Buckling of the steel frames with the I-shaped cross-section columns of variable web height - Bilyk, S. I.; Bilyk, А.S.; Nilova, T.O.; Shpynda, V. Z.; Tsyupyn, E. I. (КНУБА, 2018)
Presented is the research of the stability of portal frames made of variable I cross-sections, depending on supports fastening factors and frames elements unfastening. In the process of mathematical research examined were five different cases of fixing columns nodes of portal frames resiliently mounted in each case, the stability criteria having been defined. In addition, conducted were studies to determine the coefficients of the portal frames elements effective length calculation in finding critical load on the column. Coefficients of the effective length factor of the welded variable I cross-section columns have been obtained. The influence of brace systems on stiffening of the whole structure, stability of the unit frames as well as the overall stability of the building with computer simulation and calculation have been studied, the coefficients of the influence of the frame structure on the stability of the unit frames having been obtained.
Keywords: variable cross-section; elastic fixed-support; effective length factor; portal frame; buckling of unit frame; load factor; the department steel and wooden constructions; 624.072.33.014.2